Role of PPARα in the Control of Torpor through FGF21-NPY Pathway: From Circadian Clock to Seasonal Change in Mammals - Norio Ishida (PPAR Research)
In nature, hibernating animals encounter fasting, cold temperature and short day seasonally. Torpor is a state of decreased physiological activity in an animal, usually characterized by a reduced body temperature and rate of metabolism to adapt such a severe environment. Ablation of the central clock synchronizer, the suprachiasmatic nucleus in brain, abolishes torpor, a hibernation-like state, implicating the circadian clock involved in this seasonal change. Biologists knows well the energy source of daily heterotherms/hibernators changed from glucose to lipids in winter. Here we review several lines of evidence of a master transcriptional regulator in lipid catabolism, PPARα, in the control of torpor through FGF21-NPY pathway. This indicate the importance of circadian—and photoperiod—regulation of PPARα to tell seasons in our body.